Cognitive and Affective Mechanisms of Discrimination and Subsequent Effects on Religious Minorities: A Psychosocial Analysis - Lamha Kausar (Wah Academia Journal of Social Sciences, 2025)
Discrimination is an umbrella term for varying systematic beliefs that cause people to act questionably against certain social groups or individuals belonging to a select community. In the context of this paper, discrimination refers to any behavior that ostracizes and/or treats a social group or an individual belonging to it with either verbal, non-verbal, physical, and/or emotional attacks which can be social or political in nature. While the basis of discrimination can be of variable; ethnic, gender-based, related to disability, or race, the following study assesses the commonly occurring religious discrimination and its effects on minorities living in Pakistan. This study ties social convention to psychological presentations of behaviors that are diagnosable through thorough investigation, and thus making it easier to characterize traits that are treatable by thorough unlearning and resocialization. This study examines the psychological impact of religious identity, focusing on trauma symptoms among individuals from minority faith groups in a predominantly Muslim context. Using self-reported data from a structured questionnaire, trauma symptoms counts were compared between respondents from religious minority backgrounds and those identifying with majority faith. A one-way ANOVA revealed a statistically significant difference in trauma symptoms between the two groups, with minority participants reporting markedly higher levels of distress (F=50.4, p < .05). These results suggest that faith-based discrimination may be a contributing factor to trauma and psychological distress in minority populations. The findings highlight the urgent need for trauma-informed mental health interventions and underscore the broader implications of systemic exclusion on minority wellbeing. Furthermore, this study addresses the gaps in disciplinary research and suggests further evaluation of empirical data collected through mix method study. Further investigation is warranted to explore intersecting variables such as gender, socioeconomic status, and prior trauma exposure.